Composite material biological sensitive electrode and preparation method thereof

By building a multi -step electrochemical process to build graphene, transition metal and its oxide composite materials, optimize its performance, solve the problem of rising detection limit and narrow linear range caused by the introduction of graphene in existing technologies, and realize the improvement of sensor sensitivity And decrease on the detection limit.

CN119335028APending Publication Date: 2025-01-21BEIJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411442612.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing biosensitivity electrodes of composite materials have increased sensitivity due to the introduction of graphene, while the detection limit increases and the linear range narrows. The coverage of graphene to the transition metal surface hinders the diffusion channel of biomolecules and affects sensitivity.

Method used

Multi -step electrochemical technology builds graphene and transition metal and its oxide composite materials to optimize its performance. This process includes electrochemical stripping, electrochemical deposition, and electrochemical corrosion, ensuring that graphene contains a lot of defects and active sites, and improves the convenience of active area and biomolecular diffusion channels.

Benefits of technology

The improvement of sensor sensitivity, the expansion of the linear range, and the decrease in the detection limit, the problem of the graphene on the metal surface activity location coverage and high background current, and improved the performance and application range of the composite biological sensitive electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119335028A_ABST
    Figure CN119335028A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite materials, and particularly relates to a composite material biological sensitive electrode and a preparation method thereof. The electrode comprises graphene, transition metal and transition metal oxide. The graphene contains a large number of defects and active sites, and the graphene is not only in contact with the transition metal, but also in contact with the transition metal oxide. The composite material sensitive electrode is prepared by adopting a multi-step electrochemical process, and the typical steps are as follows: (1) preparing graphene by using an electrochemical stripping method; and (2) preparing the composite material of the graphene, the transition metal and the oxide of the transition metal by using an electrochemical deposition method. And (3) carrying out electrochemical corrosion treatment on the composite material by using an electrochemical corrosion method to obtain the composite material biological sensitive electrode. The electrode has the advantages of many active sites, large active area, short diffusion channel, high biomolecule detection sensitivity, small detection limit, large detection linear range, high performance stability, simple preparation process, controllability and strong expandability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a composite material biosensitive electrode and a preparation method thereof. Background Art

[0002] Composite materials can be composed of two or more types of materials. They are widely used in many fields because they can complement the advantages of multiple materials and have better mechanical properties, electrical properties, mechanical properties and catalytic properties than single materials. Graphene, as a typical two-dimensional material, has extremely high specific surface area and excellent comprehensive performance and is widely used in composite materials to improve the comprehensive performance of materials. Using graphene for transition metals to improve their biosensing performance has been a research hotspot in related fields in recent years. In composite materials of graphene and transition metals and their oxides, usually, transition metals and their oxides play a catalytic role and provide the main active substances, and graphene provides a large specific surface area and excellent electron transfer rate, so that the composite material system has excellent electrocatalytic activity. The use of graphene and transition metals and their oxides can increase the response sensitivity of biosensitive electrodes to glucose to 2000μA·mM. -1 cm -2 However, a common problem is that due to the large specific surface area and large response current of graphene, the background current of the corresponding biosensor is very large, which causes the detection limit of the composite material after adding graphene to increase significantly, mostly exceeding 1.5μM. On the other hand, due to similar reasons, the addition of graphene will also cause the linear range of the composite material to narrow, mostly in the range of 0.01-1.5mM. If a strategy is adopted to reduce the detection limit and increase the linear range, the sensitivity will be greatly reduced at the same time, reducing the sensitivity to less than 1000μA·mM -1 cm -2 In addition, the coverage of transition metal surfaces by graphene will not only hinder the diffusion channels of biomolecules, but also sacrifice some active substances on the transition metal surfaces, which limits the improvement of its sensitivity. Existing research has not yet found a good way to solve these problems.

[0003] The object of the present invention is to provide a composite material biosensitive electrode and a preparation method thereof, in order to solve the above problems. Summary of the invention

[0004] Based on the background technology, the present invention provides a composite biosensitive electrode and a preparation method thereof. The technical problem to be solved by the present invention is to overcome the problems in the prior art that the introduction of graphene leads to an increase in sensitivity, an increase in detection limit, and a narrowing of the linear range. The present invention proposes to construct and optimize and improve the performance of a composite material of graphene and transition metals and their oxides through a multi-step electrochemical process. The obtained composite material has more active sites, a higher active area, and a more convenient biomolecule diffusion channel than similar materials, thereby overcoming the problem of graphene covering the active sites on the surface of metals and their oxides, and the defects of high background current and high detection limit caused by graphene, which leads to limited performance and application.

[0005] To this end, the technical solution of the present invention is as follows:

[0006] A composite material biosensitive electrode, characterized in that the composite material comprises graphene (1), a transition metal (2), and a transition metal oxide (3);

[0007] The graphene (1) contains a large number of defects and active sites;

[0008] The transition metal (2) is at least one of copper, nickel, or cobalt;

[0009] The transition metal oxide (3) is at least one of cupric oxide, cuprous oxide, cupric hydroxide, nickel oxide, nickel hydroxide, cobalt oxide and cobalt hydroxide.

[0010] The graphene (1) may be a single layer, two layers or multiple layers.

[0011] The graphene (1) is in contact not only with the transition metal (2) but also with the transition metal oxide (3).

[0012] The biological substance that can be detected by the composite material biosensitive electrode may be glucose or fructose.

[0013] The composite biosensitive electrode is prepared using a multi-step electrochemical process.

[0014] A method for preparing a composite biosensitive electrode, wherein the composite biosensitive electrode is prepared by a multi-step electrochemical process, and the typical electrochemical process steps are as follows:

[0015] (1) Graphene is prepared by electrochemical stripping. Graphite foil or graphite plate is used as anode, ammonium sulfate is used as stripping solution, and stripping is performed for 10-60 minutes at a temperature range of 10-30°C and a voltage of 4-10V. The obtained graphene includes graphene films at the cathode and anode and graphene powder dispersed in the solution.

[0016] (2) Using electrochemical deposition to prepare a composite material of graphene and transition metals and their oxides. The current density of the electrochemical deposition used is 0.2-10A / dm 2 The deposition time is 1-60 minutes. During the electrochemical deposition process, the stirring is performed by using an air stirring method or a magnetic stirrer stirring method.

[0017] (3) Further treating the composite material of graphene, transition metal and its oxide by electrochemical corrosion to obtain the composite material biosensitive electrode. The electrochemical corrosion solution is a sodium hydroxide aqueous solution with a concentration of 0.01-10 mol / L, a temperature of 10-35° C., a corrosion time of 5-60 minutes, and a corrosion voltage of 4-12V.

[0018] The thickness of the anode used in the step (1) is 0.01-1 mm; the cathode used is graphite foil, copper foil or nickel foil, and its thickness is 0.01-1 mm; the concentration of the ammonium sulfate solution used is 0.05-0.25 mol / L; the graphene film can be used directly; the graphene powder dispersed in the solution is washed in pure water, then filtered through filter paper, and finally dried at 40-60° C. for 1-24 hours to prepare graphene powder for standby use.

[0019] In the step (2), the cathode is copper foil or nickel foil or graphene film or metal foil covered with graphene film, and the anode is graphite or phosphor copper sheet or nickel plate or platinum wire; the plating solution contains at least one of copper plating solution or nickel plating solution or cobalt plating solution, and when the plating solution contains two or more metal ions, the concentration ratio of any two metal ions is between 0.1-10; the plating solution also contains a surfactant, and the surfactant is sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate, and the concentration is 0.001-0.2g / L; graphene powder can also be added to the plating solution, and the concentration of the graphene powder is 0-0.5g / L. When using, the metal plating solution containing the surfactant is first used to wet, let it stand for 5-60 minutes, then ultrasonically disperse for 15-30 minutes, and then added to the metal plating solution; the main components of the copper plating solution are Copper sulfate pentahydrate (CuSO4·5H2O) may also contain sulfuric acid and other ingredients, wherein the concentration of CuSO4·5H2O is 50-250g / L and the concentration of sulfuric acid is 25-100g / L; the nickel plating solution mainly contains nickel sulfate heptahydrate (Ni(SO4)2·7H2O) or nickel chloride hexahydrate (NiCl2·6H2O), and may also contain boric acid (H3BO4), wherein the concentration of nickel sulfate heptahydrate is 50-400g / L, the concentration of nickel chloride hexahydrate is 10-300g / L, and the concentration of boric acid is 10-40g / L; the cobalt plating solution mainly contains cobalt chloride hexahydrate (CoCl2·6H2O) and boric acid and other ingredients, wherein the concentration of CoCl2·6H2O is 10-100g / L, and the component of boric acid is 10-60g / L.

[0020] In step (3), the cathode is the electrode to be corroded, and the anode is copper foil or nickel foil or platinum wire or graphite; the electrode to be corroded can be a graphene film or a metal film or a metal film covered with graphene or a composite film of graphene and transition metals and their oxides.

[0021] A composite material biosensitive electrode and a preparation method thereof. The morphology, composition and performance of the composite material can also be regulated by an annealing process. The typical annealing process is 100-500°C for 5-60 minutes.

[0022] The technical solution of the present invention has the following advantages:

[0023] 1. The present invention uses graphene to load transition metals and their oxides. The high specific surface area of ​​graphene increases the amount of active substances dispersed thereon, which is beneficial to the improvement of sensor sensitivity. At the same time, the graphene of the present invention contains a large number of defects, which can not only serve as active sites for biomolecules, but also facilitate the diffusion of biomolecules through graphene through these defects, reducing the negative impact of graphene preventing biomolecules from passing through, thereby shortening the diffusion path of biomolecules, and thus obtaining an improvement in sensor sensitivity, an expansion of the linear range, and a reduction in the detection limit.

[0024] 2. The composite biosensitive electrode provided by the present invention can realize the mutual dispersion of graphene and transition metals and their oxides. The contact between graphene and transition metal oxides can reduce the contact probability between graphene and transition metals, which can not only effectively play the auxiliary role of graphene's high electron mobility, but also effectively overcome the degradation of graphene's electron mobility and other properties caused by the strong interaction between graphene and transition metals.

[0025] 3. The composite biosensitive electrode provided by the present invention is prepared using a multi-step electrochemical process, which has a simple process, controllable performance and low cost.

[0026] 4. The present invention provides a composite material biosensitive electrode, wherein the graphene has a good ability to prevent further oxidation of transition metals in the composite material, thereby greatly improving the stability of the composite material biosensitive electrode.

[0027] 5. The preparation process of the composite biosensitive electrode provided by the present invention has strong scalability, and the composition, surface morphology and defects, and degree of crystallization of the composite material can be adjusted through processes such as annealing, thereby further optimizing and improving the biosensing performance of the composite electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] The accompanying drawings are schematic diagrams of the structure of the composite material sensitive electrode of the present invention: (1) using graphene as the substrate and the plating solution does not contain graphene; (2) using graphene as the substrate and the plating solution contains graphene; (3) using a transition metal with graphene peeled off as the substrate and the plating solution does not contain graphene; (4) using a transition metal with graphene peeled off as the substrate and the plating solution contains graphene.

[0030] The accompanying drawings are marked as follows:

[0031] 1-graphene; 2-transition metal; 3-transition metal oxide. DETAILED DESCRIPTION

[0032] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0033] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0034] Example 1.

[0035] This embodiment provides a composite biosensitive electrode and a preparation method thereof, such as Figure 1 As shown, the present invention loads transition metals and their oxides on graphene. The high specific surface area of ​​graphene increases the amount of active substances dispersed thereon. The defects in the graphene can not only serve as active sites for biomolecules, but also facilitate the diffusion of biomolecules through the graphene, thereby reducing the negative impact of graphene preventing the passage of biomolecules and shortening the diffusion path of biomolecules, thereby achieving improved sensor sensitivity, expanded linear range and reduced detection limit.

[0036] A composite material biosensitive electrode, characterized in that the composite material comprises graphene (1), a transition metal (2), and a transition metal oxide (3);

[0037] The graphene (1) contains a large number of defects and active sites;

[0038] The transition metal (2) is at least one of copper, nickel, or cobalt;

[0039] The transition metal oxide (3) is at least one of cupric oxide, cuprous oxide, cupric hydroxide, nickel oxide, nickel hydroxide, cobalt oxide and cobalt hydroxide.

[0040] The graphene (1) may be a single layer, two layers or multiple layers.

[0041] The graphene (1) is in contact not only with the transition metal (2) but also with the transition metal oxide (3).

[0042] Example 2.

[0043] Graphene was prepared by electrochemical stripping, with 0.1 mm thick graphite foil as cathode, 0.2 mm thick graphite foil as anode, 0.2 mol / L ammonium sulfate solution as stripping solution, and stripping at 10V voltage for 10 minutes at 10°C to obtain graphene film and graphene powder dispersed in the solution. The graphene powder was washed in pure water, filtered through filter paper, and finally dried at 60°C for 12 hours to prepare graphene powder for standby use. The plating solution was prepared by mixing 100 g / L of copper sulfate pentahydrate (CuSO4·5H2O), 50 g / L of sulfuric acid (H2SO4), 200 g / L of nickel sulfate heptahydrate (Ni(SO4)2·7H2O), 150 g / L of nickel chloride hexahydrate (NiCl2·6H2O), 20 g / L of boric acid (H3BO4), and 0.2 g / L of sodium dodecyl sulfate. 0.5 g / L graphene powder was wetted with the prepared plating solution, left to stand for 60 minutes, then ultrasonically dispersed for 30 minutes, and added to the plating solution to obtain a mixed plating solution. Copper foil was used as the cathode, nickel plate was used as the anode, and the mixed plating solution with graphene was used as the plating solution at 0.2 A / dm 2 The solution was deposited at a current density of 30 minutes, and a magnetic stirrer was used to stir the solution at a speed of 100 rpm during the deposition process to obtain a composite material of graphene and transition metals and their oxides. The composite material was used as the cathode, the platinum wire was used as the anode, and a 10 mol / L sodium hydroxide aqueous solution was used as the corrosion solution. Electrochemical corrosion was carried out at 10V and 30°C for 30 minutes to obtain a composite biosensitive electrode of graphene and copper nickel and their oxides. The sensitivity of the glucose sensor measured using the current-time curve using the electrode as the working electrode, the platinum wire as the counter electrode, and Ag / AgCl as the reference electrode was 2100μA·mM -1 cm -2 , the detection limit was 0.07 μM and the linear range was 0.05-2.5 mM.

[0044] Example 3.

[0045] Graphene was prepared by electrochemical exfoliation, with 0.025 mm thick copper foil as cathode and 0.5 mm thick graphite foil as anode. The graphene film was obtained by exfoliation in 0.1 mol / L ammonium sulfate solution at 25°C for 60 minutes using 4V voltage. The plating solution was prepared by mixing 50 g / L copper sulfate pentahydrate CuSO4·5H2O, 25 g / L sulfuric acid (H2SO4), 50 g / L nickel sulfate heptahydrate (Ni(SO4)2·7H2O), 10 g / L nickel chloride hexahydrate (NiCl2·6H2O), 10 g / L boric acid (H3BO4), and 0.001 g / L sodium dodecylbenzene sulfonate. The graphene film on the copper foil was used as cathode, graphite as anode, and the mixed plating solution as plating solution at 0.2 A / dm 2 The electrode was deposited at a current density of 40 minutes, and the deposition process was stirred by air stirring to obtain a composite material of graphene and transition metals and their oxides. The composite material was used as the cathode, the phosphor copper sheet was used as the anode, and 0.01 mol / L sodium hydroxide was used as the corrosion solution. Electrochemical corrosion was carried out at 4V and 10°C for 60 minutes to obtain a composite biosensitive electrode of graphene and copper nickel and their oxides. The electrode was used as the working electrode, the platinum wire was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The sensitivity of the glucose sensor measured using the current-time curve was 2600μA·mM -1 cm -2 , the detection limit was 0.15 μM and the linear range was 0.05-3.5 mM.

[0046] Example 4.

[0047] Graphene was prepared by electrochemical exfoliation, with nickel foil as cathode, 0.5 mm graphite foil as anode, and 0.25 mol / L ammonium sulfate solution as exfoliation solution. The exfoliation was performed at 10V voltage at 20°C for 50 minutes to obtain a graphene film on the nickel foil. The plating solution was prepared by mixing 50 g / L cobalt chloride hexahydrate (CoCl2·6H2O), 20 g / L boric acid (H3BO4), and 0.1 g / L sodium dodecyl sulfate. The nickel foil covered with graphene was used as cathode and platinum wire as anode. The graphene film was electrochemically exfoliated at 1A / dm 2 The solution was deposited at a current density of 20 minutes, and a magnetic stirrer was used to stir the solution at a speed of 100 rpm during the deposition process to obtain a composite material of graphene, cobalt, nickel and its oxides. The composite material was used as the cathode, nickel foil was used as the anode, and 1 mol / L 20°C sodium hydroxide was used as the corrosion solution. Electrochemical corrosion was performed at 9V for 5 minutes to obtain the composite biosensitive electrode. The sensitivity of the fructose sensor measured using the current-time curve was 500μA·mM using the electrode as the working electrode, the platinum wire as the counter electrode, and Ag / AgCl as the reference electrode. -1 cm-2 , the detection limit was 0.28 μM and the linear range was 0.05-1.5 mM.

[0048] Example 5.

[0049] Graphene was prepared by electrochemical stripping, with copper foil as cathode, 1 mm graphite foil as anode, 0.1 mol / L ammonium sulfate solution as stripping solution, and stripping at 10V voltage for 20 minutes at 25°C to obtain graphene film and graphene powder dispersed in the solution. The graphene powder was washed in pure water, filtered through filter paper, and finally dried at 40°C for 24 hours to prepare graphene powder for standby use. The plating solution was prepared by mixing 50g / L of copper sulfate pentahydrate CuSO4·5H2O, 50g / L of sulfuric acid (H2SO4), 400g / L of nickel sulfate heptahydrate Ni(SO4)2·7H2O, 100g / L of nickel chloride hexahydrate (NiCl2·6H2O), 40g / L of boric acid (H3BO4), and 0.5g / L of sodium dodecyl sulfate. 0.01 g / L graphene powder was wetted with the prepared plating solution, left to stand for 5 minutes, then ultrasonically dispersed for 15 minutes, and added to the plating solution to obtain a mixed plating solution. The graphene on the copper foil was used as the cathode, the nickel plate was used as the anode, and the mixed plating solution with graphene added was used as the plating solution. The plating solution was heated at 10 A / dm 2 The solution was deposited at a current density of 100 for 1 minute. During the deposition process, a magnetic stirrer was used to stir the solution at a speed of 100 rpm to obtain a composite material of graphene, transition metals and their oxides. The composite material was used as the cathode, nickel foil was used as the anode, and 0.5 mol / L sodium hydroxide was used as the corrosion solution. The composite material biosensitive electrode was obtained by electrochemical corrosion at 9V and 30°C for 10 minutes. The sensitivity of the fructose sensor measured by the current-time curve using the electrode as the working electrode, the platinum wire as the counter electrode, and Ag / AgCl as the reference electrode was 600μA·mM -1 cm -2 , the detection limit was 0.35 μM and the linear range was 0.05-2 mM.

[0050] Example 6.

[0051] Graphene was prepared by electrochemical stripping, with 0.1 mm thick graphite foil as cathode, 1 mm graphite plate as anode, 0.25 mol / L ammonium sulfate solution as stripping solution, and stripping at 10V voltage for 10 minutes at 28°C to obtain graphene film and graphene powder dispersed in the solution. The graphene powder was washed in pure water, filtered through filter paper, and finally dried at 50°C for 8 hours to prepare graphene powder for standby use. The plating solution was prepared by mixing 50g / L of copper sulfate pentahydrate CuSO4·5H2O, 20g / L of sulfuric acid (H2SO4), 100g / L of nickel sulfate heptahydrate Ni(SO4)2·7H2O, 100g / L of nickel chloride hexahydrate (NiCl2·6H2O), 20g / L of boric acid (H3BO4), and 0.1g / L of sodium dodecyl sulfate. 0.1 g / L graphene powder was wetted with the prepared plating solution, left to stand for 60 minutes, then ultrasonically dispersed for 30 minutes, and added to the plating solution to obtain a mixed plating solution. The graphene film at the anode was used as the cathode, the nickel foil was used as the anode, and the mixed plating solution with graphene added was used as the plating solution at 0.5 A / dm 2 The solution was deposited at a current density of 30 minutes, and a magnetic stirrer was used to stir the solution at a speed of 50 rpm during the deposition process to obtain a composite material of graphene, copper nickel and its oxides. The obtained composite material was annealed at 200°C for 10 minutes. The annealed composite material was used as the cathode, graphite was used as the anode, and 1 mol / L 30°C sodium hydroxide was used as the corrosion solution. Electrochemical corrosion was performed at 9V for 15 minutes to obtain the composite biosensitive electrode. The sensitivity of the glucose sensor measured using the current-time curve using the electrode as the working electrode, the platinum wire as the counter electrode, and Ag / AgCl as the reference electrode was 4200μA·mM -1 cm -2 , the detection limit was 0.02 μM and the linear range was 0.05-3.5 mM.

[0052] Example 7.

[0053] Graphene was prepared by electrochemical exfoliation, with a 0.1 mm thick graphite foil as the cathode, a 1 mm thick graphite foil as the anode, and a 0.1 mol / L ammonium sulfate solution as the exfoliation solution. The graphene film was obtained by exfoliation at 25°C for 30 minutes using a 10V voltage. The plating solution was prepared by mixing 20 g / L nickel sulfate heptahydrate Ni(SO4)2·7H2O, 15 g / L nickel chloride hexahydrate (NiCl2·6H2O), 10 g / L boric acid (H3BO4), and 0.2 g / L sodium dodecyl sulfate. The graphene obtained at the cathode was used as the cathode, and the platinum wire was used as the anode. The graphene film was obtained by electrochemical exfoliation at 2A / dm 2The solution was deposited at a current density of 40 minutes, and a magnetic stirrer was used to stir the solution at a speed of 50 rpm during the deposition process to obtain a composite material of graphene, nickel and its oxide. The composite material was used as the cathode, the platinum wire was used as the anode, and 0.1 mol / L 25°C sodium hydroxide was used as the corrosion solution. The composite material biosensitive electrode was obtained by electrochemical corrosion at 6V for 30 minutes. The sensitivity of the glucose sensor measured by the current-time curve using the electrode as the working electrode, the platinum wire as the counter electrode, and Ag / AgCl as the reference electrode was 3100μA·mM -1 cm -2 , the detection limit was 0.09 μM and the linear range was 0.05-4.5 mM.

[0054] Example 8.

[0055] Graphene was prepared by electrochemical exfoliation, with a 0.1 mm thick graphite foil as the cathode, a 1 mm thick graphite foil as the anode, and a 0.1 mol / L ammonium sulfate solution as the exfoliation solution. The graphene film was obtained by exfoliation at 25°C for 30 minutes using a 10V voltage. The plating solution was prepared by mixing 50 g / L of copper sulfate pentahydrate CuSO4·5H2O, 20 g / L of sulfuric acid (H2SO4), 100 g / L of nickel sulfate heptahydrate Ni(SO4)2·7H2O, 100 g / L of nickel chloride hexahydrate (NiCl2·6H2O), 10 g / L of cobalt chloride hexahydrate (CoCl2·6H2O), 20 g / L of boric acid (H3BO4), and 0.1 g / L of sodium dodecyl sulfate. The graphene obtained at the cathode was used as the cathode, and graphite was used as the anode. The electrochemical exfoliation was performed at 2A / dm 2 The solution was deposited at a current density of 40 minutes, and a magnetic stirrer was used to stir the solution at a speed of 50 rpm during the deposition process to obtain a composite material of graphene, copper-nickel-cobalt and its oxides. The composite material was used as the cathode, the platinum wire was used as the anode, and 0.1 mol / L 25°C sodium hydroxide was used as the corrosion solution. The composite material biosensitive electrode was obtained by electrochemical corrosion at 6V for 30 minutes. The sensitivity of the glucose sensor measured by the current-time curve using the electrode as the working electrode, the platinum wire as the counter electrode, and Ag / AgCl as the reference electrode was 2600μA·mM -1 cm -2 , the detection limit was 0.11 μM and the linear range was 0.05-3 mM.

[0056] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A composite biosensitive electrode, characterized in that: The composite material comprises graphene (1), a transition metal (2), and a transition metal oxide (3); The graphene (1) contains a large number of defects and active sites; The transition metal (2) is at least one of copper, nickel, or cobalt; The transition metal oxide (3) is at least one of cupric oxide, cuprous oxide, cupric hydroxide, nickel oxide, nickel hydroxide, cobalt oxide and cobalt hydroxide.

2. A composite biosensitive electrode according to claim 1, characterized in that: The graphene (1) is a single layer, two layers or multiple layers; the graphene (1) is not only in contact with the transition metal (2), but also in contact with the transition metal oxide (3).

3. The composite biosensitive electrode according to claim 1, characterized in that: The biological substance that can be detected by the composite material biosensitive electrode may be glucose or fructose.

4. A method for preparing a composite biosensitive electrode, characterized in that: The composite biosensitive electrode is prepared by a multi-step electrochemical process, and its typical electrochemical process steps are as follows: (1) Graphene is prepared by electrochemical stripping. Graphite foil or graphite plate is used as anode, ammonium sulfate is used as stripping solution, and stripping is performed for 10-60 minutes at a temperature range of 10-30°C and a voltage of 4-10V. The obtained graphene includes graphene films at the cathode and anode and graphene powder dispersed in the solution. (2) Using electrochemical deposition to prepare a composite material of graphene and transition metals and their oxides. The current density of the electrochemical deposition used is 0.2-10A / dm 2 , the deposition time is 1-60 minutes. During the electrochemical deposition process, stirring is performed using an air stirring method or a magnetic stirrer stirring method. (3) The composite material of graphene, transition metal and its oxide is subjected to electrochemical corrosion treatment by an electrochemical corrosion method to obtain the composite material biosensitive electrode. The electrochemical corrosion solution is a sodium hydroxide aqueous solution with a concentration of 0.01-10 mol / L, a temperature of 10-35° C., a corrosion time of 5-60 minutes, and a corrosion voltage of 4-12V.

5. The method for preparing a composite material biosensitive electrode according to claim 4, characterized in that: The thickness of the anode used in step (1) is 0.01-1 mm; the cathode used is graphite foil, copper foil or nickel foil, and its thickness is 0.01-1 mm; the concentration of the ammonium sulfate solution used is 0.05-0.25 mol / L.

6. The method for preparing a composite biosensitive electrode according to claim 4, characterized in that: The graphene film in step (1) can be used directly; the graphene powder dispersed in the solution is washed in pure water, filtered through filter paper, and finally dried at 40-60° C. for 1-24 hours to prepare graphene powder for standby use.

7. The method for preparing a composite biosensitive electrode according to claim 4, characterized in that: In the electrochemical deposition method described in step (2), the cathode is copper foil or nickel foil or graphene film or metal foil covered with graphene film, and the anode is graphite or copper foil or nickel foil or platinum wire; the plating solution contains at least one of copper plating solution or nickel plating solution or cobalt plating solution; when the plating solution contains two or more metal ions, the concentration ratio of any two metal ions is between 0.1-10; the plating solution also contains a surfactant, which is sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate, with a concentration of 0.001-0.2 g / L; graphene powder can also be added to the plating solution, and the concentration of the graphene powder is 0-0.5 g / L; when the graphene powder is used, it is first wetted with the metal plating solution containing the surfactant, left to stand for 5-60 minutes, then ultrasonically dispersed for 15-30 minutes, and then added to the metal plating solution.

8. The method for preparing a composite material biosensitive electrode according to claim 4, characterized in that: The copper plating solution in step (2) mainly comprises copper sulfate pentahydrate (CuSO4·5H2O), and may further comprise sulfuric acid and other components, wherein the concentration of CuSO4·5H2O is 50-250 g / L, and the concentration of sulfuric acid is 25-100 g / L; the nickel plating solution mainly comprises nickel sulfate heptahydrate (Ni(SO4)2·7H2O) or nickel chloride hexahydrate (NiCl2·6H2O), and may further comprise boric acid (H3BO4), wherein the concentration of nickel sulfate heptahydrate is 50-400 g / L, the concentration of nickel chloride hexahydrate is 10-300 g / L, and the concentration of boric acid is 10-40 g / L; the cobalt plating solution mainly comprises cobalt chloride hexahydrate (CoCl2·6H2O) and boric acid and other components, wherein the concentration of CoCl2·6H2O is 10-100 g / L, and the concentration of boric acid is 10-60 g / L.

9. The method for preparing a composite material biosensitive electrode according to claim 4, characterized in that: In the electrochemical corrosion modification process described in step (3), the cathode is the electrode to be corroded, and the anode is copper foil or nickel foil or platinum wire or graphite; the electrode to be corroded can be a graphene film or a metal film or a metal film covered with graphene or a composite film of graphene and transition metals and their oxides.

10. A composite material biosensitive electrode and a preparation method thereof according to claims 1 and 4, characterized in that: The morphology, composition and performance of the composite material can also be regulated by an annealing process.